Practice, and Barriers to Spirometry Usage among Healthcare Professionals in Karachi: Practice, and Barriers to Spirometry Usage among Healthcare Professionals - Patoli, Zoha Soomar; Zaman, Bushra Marium; Mengal, Saba; Arzoo, Obaida; Anwar, Farheen; Zafar, Ahmar; Shamim, Javeria; Ali, Sabina Anwer; Irshad, Anum; Baqir, Syeda Rida (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
A spirometer is the most suitable technique for primary care because it is very convenient for healthcare professionals to use because it is very low cost, performs in a short time, and also it is a non-invasive technique patients can easily understand and perform. The usage of a spirometer is very beneficial and important to find out the stage and monitor the pulmonary conditions during performing therapies. Objective: To determine the knowledge, practice, and barriers regarding the usage of spirometry among healthcare professionals in Karachi. Methods: A cross-sectional survey was done from Nov 2023 to April 2024 in Karachi on healthcare professionals to explore the usage of spirometry among them. The sample size was 384 and the non-probability convenients sampling was used. Data were evaluated through a validated questionnaire and analization of data were done through SPSS version 23.0. Results: A total number of 384 research participants were included in this study. The results showed that knowledge related to spirometry usage was present in research participants around 319 (83.07%). The practice of spirometry by healthcare professionals was observed in 172 (58.9%) and the most common barrier observed in this study was the rate of unavailability of the equipment around 51 (13.28%) in the hospitals. Conclusion: It was concluded that the knowledge of spirometry was good among healthcare professionals but the practice was poor due to the unavailability of spirometry in the hospitals.